Analisis Hukum Bisnis Tentang Kerugian Keuangan Pada Badan Usaha Milik Negara (BUMN) (International Forum of Researchers and Lecturers, 2024)
State assets in BUMN are State Finance, namely state money which is separated into its management as a form of direct capital participation from the state. BUMN is a business entity so it is a business entity whose business orientation is focused on making a profit (profit). The problem is that not all BUMNs in Indonesia are said to be good and healthy BUMNs, because a number of BUMNs are still suffering significant or even very large losses. Quite a few of the BUMNs in question suffer losses due to various factors, so that if losses occur to the BUMN, then these losses constitute losses to the State Finances and qualify as a criminal act of corruption. From the research results, it can be concluded that state finances in state-owned companies are realized in the criteria if all the capital comes from separated state assets, and if the majority (majority) of the capital comes from separated state assets. These two criteria indicate the existence of state assets in state-owned companies so that they are fully subject to the legal provisions of state-owned companies according to Law no. 19 of 2003. State financial losses to state-owned companies are not state financial losses, but rather losses to the state-owned companies themselves. Thus, these financial losses are subject to the provisions of private law as regulated in Law no. 19 of 2003 and Law no. 40 of 2007 concerning PT